2017
DOI: 10.1177/0020764017695576
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of depression among garment workers in Bangladesh

Abstract: Depression is a multifaceted health issue with many personal, social, economic and health determinants and consequences. This study demonstrates that the prevalence of moderate-to-severe depression among working women in Bangladesh is quite high. Prevention and treatment of depression in developing countries and societies can reduce suffering, lower incidence of suicide, and prevent economic loss. Creating awareness on outsourced workers' poor mental health may help in developing initiatives to protect and pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 47 publications
2
34
2
Order By: Relevance
“…Our finding was comparable to a prior finding among industrial workers in Hanoi and Bac Ninh, Vietnam (38.6%-PHQ-9) [20], but approximately 1.5 times higher compared to workers in shoe-making factories in Hai Phong, Vietnam (18.8%) [25]. In addition, this prevalence was relatively higher than that of factory workers in other developing countries such as Bangladesh (20.9% in garment workers) [8] or India (0% in general factory workers but 36% had anxiety disorders and 18% had stress) [35] but equal to the result in China (31.7% in shoe-making workers) [14] and Malaysia (35.4% in automotive assembly workers) [11]. Notably, our result indicated that one-third of our sample had suicidal ideation in the last two weeks, which was more than four times higher when compared with the rate of suicidal ideation in the general Vietnamese population (8.9%) [36].…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Our finding was comparable to a prior finding among industrial workers in Hanoi and Bac Ninh, Vietnam (38.6%-PHQ-9) [20], but approximately 1.5 times higher compared to workers in shoe-making factories in Hai Phong, Vietnam (18.8%) [25]. In addition, this prevalence was relatively higher than that of factory workers in other developing countries such as Bangladesh (20.9% in garment workers) [8] or India (0% in general factory workers but 36% had anxiety disorders and 18% had stress) [35] but equal to the result in China (31.7% in shoe-making workers) [14] and Malaysia (35.4% in automotive assembly workers) [11]. Notably, our result indicated that one-third of our sample had suicidal ideation in the last two weeks, which was more than four times higher when compared with the rate of suicidal ideation in the general Vietnamese population (8.9%) [36].…”
Section: Discussionsupporting
confidence: 78%
“…Another study in Korea found that unskilled male workers had a three times higher rate of suicide-related mortality compared to skilled male workers [19]. Despite these variations, all studies confirmed that the prevalence of depression and suicidal ideation in industrial workers was remarkably higher than that of the general population, as well as the need of the depression screening and risk reduction programs [8,11,14]. These results suggest the necessity of appropriate interventions to screen, control, and improve depression in this vulnerable group.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Indeed, we found that among those who have low job strain at baseline, nonparticipants due to missing data on job strain were more likely to be older (60–63 years) and with higher levels of depression at the 2‐year follow‐up. These relatively healthy participants in this subpopulation could have been exposed to less risk factors compared with nonparticipants, which could underestimate the association between baseline depression and job strain incidence as these factors were strongly associated with depression (Fitch et al, ) and elevated job strain (De Lange et al, ; Shigemi, Mino, & Tsuda, ). On the other hand, individuals who recovered from depression and those who had effective treatment might have higher levels of tolerance to high job strain, so that they might not experience high strain even if the strain was high.…”
Section: Discussionmentioning
confidence: 99%